ОСОБЛИВОСТІ РОЗПОДІЛІВ ЗА ДІАМЕТРАМИ ОТРИМАНИХ ЗА СУБМІЛІСЕКУНДНІЙ ТРИВАЛОСТІ РОЗРЯДНИХ ІМПУЛЬСІВ ІСКРОЕРОЗІЙНИХ ЧАСТИНОК АЛЮМІНІЮ І ЛУНОК НА ПОВЕРХНІ ЙОГО ГРАНУЛ - Шидловська, Н.А.; Захарченко, С.М.; Перекос, А.О. (Інститут електродинаміки НАН України, Київ, 2021)
The conditions and technique for obtaining single-mode size distributions of spark-erosive aluminum particles are given. The statistical parameters of the size distributions of spark-erosive aluminum particles and caverns on the surface of its granules, obtained at a submilisecond duration of discharge pulses were calculated. A comparative analysis of the volumes of metal of erosion caverns and particles is carried out. The agreement of the diameter distributions of spark-erosive particles and caverns obtained in practice with the following theoretical distributions of a continuous random variable: Gauss, Weibull, the integral of the Rosin-Rammler function, and also log-normal distribution is verified. In this case, the parameters of theoretical distributions were calculated both by the statistical parameters of the distributions obtained in practice, and by the criterion of the smallest value of the average module of the relative deviation of the theoretical and practical distributions. It has been shown that for the values of the parameters of theoretical distributions that correspond to the statistical parameters of practical distributions, the distribution of erosive particles by diameters is in the best agreement with the Gauss distribution, and the caverns – with the distribution of integral of the Rosin-Rammler function. References 27, figures 2, tables 3.